The prevalence and concentration of aflatoxins in beers: a global systematic review and meta-analysis and probabilistic health risk assessment. - Fakhri, Yadolah; Ranaei, Vahid; Pilevar, Zahra; Moradi, Mahboobeh; Mahmoudizeh, Amirhossein; Hemmati, Fatemeh; Mousavi Khaneghah, Amin (International Journal of Environmental Health Research, 2025)
Mycotoxins have been identified as considerable contaminants in beer. The current investigation's concentration and prevalence of aflatoxins (AFs) in beer were meta-analyzed. The health risk of consumers was estimated through MOEs in the Monte Carlo simulation (MCS) model. The rank order of AFs in beer based on pooled prevalence was AFB1 (26.00%) > AFG1 (14.93%) > AFB2 (7.69%) > AFG2 (7.52%), In addition, the rank order of AFs in beer based on their pooled concentration was AFG1 (0.505 µg/l) > AFB1 (0.469 µg/l) > AFB2 (0.134 µg/l) > AFG2 (0.071 µg/l). The prevalence and concentration of AFs in beer in Malawi were higher than in other countries. The health risk assessment shows consumers in all countries, especially Malawi, Brazil, and Cameroon, are exposed to unacceptably health risks (MOEs <10,000). It is recommended to monitor levels of AFs in beer efficiently and implement control plans in order to decrease health risk of exposed population.